Fatherless Impact on Jambi University Guidance and Counseling Study Program Students - Muhammad Alridho Lubis; Aria Dwi Riski; Diana Nopita; Dwi Ayu Apriliana; Willujeng Kurniati; Khadijah Ainul Mutmainnah (International Research-Based Education Journal, 2024)
The purpose of this study was to discover and study the effects of paternal absence on Jambi University Guidance and Counseling (BK) students. The method used is qualitative and case studies are used. Data was collected through thorough interviews with BK students who did not have fathers. A thorough interview with a student who experienced a life without a father, where his father's role was lost due to divorce, showed that the student was very sad when he saw the interaction of father and son other people around him. They miss the warmth and care they should have felt when they were little. The absence of fathers has an impact on emotional and psychological development, such as difficulty controlling emotions, frequent mood shifts, and feeling stressed because the role of fathers cannot speak or vent feelings. Despite the efforts of other family members, such as grandmothers and grandfathers who motivate students by replacing financial responsibilities. The dream and hope related to the future life is to build a strong family with his children who will not experience what he experienced before. According to this student, a father must be responsible for the education of the child and meet all his needs mentally and financially.